Diaquabis(2-bromobenzoato-κO)bis(N,N-diethylnicotinamide-κN1)manganese(II) - Hacali Necefoğlu; F. Elif Özbek; Barış Tercan; Hakan Dal; Tuncer Hökelek (Acta Crystallographica Section E, 2009)
The title MnII complex, [Mn(C7H4BrO2)2(C10H14N2O)2(H2O)2], is centrosymmetric. The molecule contains two 2-bromobenzoate (BB) and two diethylnicotinamide (DENA) ligands and two water molecules, all ligands being monodentate. The four O atoms in the equatorial plane around the Mn atom form a slightly distorted square-planar arrangement, while the distorted octahedral coordination is completed by the two N atoms of the DENA ligands in the axial positions. The dihedral angle between the carboxyl group and the adjacent benzene ring is 79.95 (11)°, while the pyridine and benzene rings are oriented at a dihedral angle of 45.66 (6)°. In the crystal structure, intermolecular O—H...O hydrogen bonds link the molecules into infinite chains.